Studi Tentang Penyebaran Pohon Ulin (Eusideroxylon Zwageri Teijsm. & Binn.) Di Taman Nasional Kutai Kalimantan Timur - Arbain, Arbain (Sekolah Tinggi Pertanian Kutai Timur, 2015)
This study aims to determine the distribution pattern (dispersion) ironwood tree, method used in this research is to make the plot to determine the pattern of spread of ironwood trees, as many as 30 plots in Sangkima and 30 plots in Prevab, each plot measuring 20x20 m. The results obtained for the deployment of ironwood based calculation Id Morisita's and the results tested by Chi-square then proceeds to forest areas Sangkima is a random approach to cluster it is influenced by the topography in Sangkima hilly fallen fruit rolled down so that out of the projected tree crown , whereas in Prevab is really clumped because of the relatively flat topography collect fallen fruit in the canopy projection only. The conclusion is clumped distribution pattern ironwood and advice is necessary to Ironwood distribution or fruit saplings to be planted to the place where I have ever experienced interference whether natural or man-made such as fallow.